Advertisement

Equivalent properties of a reverse half-discrete Hilbert’s inequality

  • Ai-zhen WangEmail author
  • Bi-cheng Yang
  • Qiang Chen
Open Access
Research
  • 106 Downloads

Abstract

By using the weight functions, the idea of introduced parameters and the Euler–Maclaurin summation formula, a reverse half-discrete Hilbert’s inequality with the homogeneous kernel and the reverse equivalent forms are given (for \({p<0}\), \({0< q<1}\)). The equivalent statements of the best possible constant factor related to a few parameters are considered. As applications, two corollaries about the case of the non-homogeneous kernel and some particular cases are obtained.

Keywords

Weight function Half-discrete Hilbert’s inequality Parameter Euler–Maclaurin summation formula Reverse 

MSC

26D15 

1 Introduction

If \(0 < \sum_{m = 1}^{\infty } a_{m}^{2} < \infty \) and \(0 < \sum_{n = 1} ^{\infty } b_{n}^{2} < \infty \), then we have the following discrete Hilbert inequality with the best possible constant factor π (cf. [1], Theorem 315):
$$ \sum_{m = 1}^{\infty } \sum _{n = 1}^{\infty } \frac{a_{m}b_{n}}{m + n} < \pi \Biggl(\sum _{m = 1}^{\infty } a_{m}^{2} \sum_{n = 1}^{\infty } b_{n}^{2} \Biggr)^{1/2}. $$
(1)
Assuming that \(0 < \int _{0}^{\infty } f^{2}(x)\,dx < \infty \) and \(0 < \int _{0}^{\infty } g^{2}(y) \,dy < \infty \), we have the following Hilbert integral inequality (cf. [1], Theorem 316):
$$ \int _{0}^{\infty } \int _{0}^{\infty } \frac{f(x)g(y)}{x + y}\,dx\,dy < \pi \biggl( \int _{0}^{\infty } f^{2}(x)\,dx \int _{0}^{\infty } g^{2}(y) \,dy \biggr)^{1/2}, $$
(2)
where the constant factor π is the best possible. Inequalities (1) and (2) are important in analysis and its applications (cf. [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13]).
We still have the following half-discrete Hilbert-type inequality (cf. [1], Theorem 351): If \(K(x)\) (\(x > 0\)) is a decreasing function, \(p > 1\), \(\frac{1}{p} + \frac{1}{q} = 1\), \(0 < \phi (s) = \int _{0}^{\infty } K(x)x ^{s - 1} \,dx < \infty \), then
$$ \sum_{n = 1}^{\infty } n^{p - 2}\biggl( \int _{0}^{\infty } K (nx)f(x)\,dx\biggr)^{p} < \phi ^{p}\biggl(\frac{1}{q}\biggr) \int _{0}^{\infty } f^{p} (x)\,dx. $$
(3)

In recent years, some new extensions of (3) were provided by [14, 15, 16, 17, 18, 19].

In 2006, using the Euler–Maclaurin summation formula, Krnic et al. [20] gave an extension of (1) with the kernel \(\frac{1}{(m + n)^{\lambda }}\) (\(0 < \lambda \le 14\)), and, in 2019, according to [20], Adiyasuren et al. [21] considered an extension of (1) involving the partial sums. In 2016–2017, by applying the weight functions, Hong [22, 23] considered some equivalent statements of the extensions of (1) and (2) with a few parameters and conjugate exponents. Some similar work was presented by [24, 25, 26].

In this paper, according to [20, 22], by the use of the weight functions, the idea of introduced parameters and the Euler–Maclaurin summation formula, a reverse half-discrete Hilbert inequality with the homogeneous kernel \(\frac{1}{(x + n)^{\lambda }}\) (\(0 < \lambda \le 28\)) and the reverse equivalent forms are given. The equivalent statements of the best possible constant factor related to a few parameters are considered. As applications, two corollaries about the cases of non-homogeneous kernel and some particular cases are obtained.

2 Some lemmas

In what follows, we assume that \(p < 0\) (\(0 < q < 1\)), \(\frac{1}{p} + \frac{1}{q} = 1\), \(\lambda \in (0,28]\), \(\sigma \in (0,2] \cap (0,\lambda )\), \(\mu \in (0,\lambda )\), \(f(x) \ge 0\) (\(x \in R_{ +} = (0,\infty )\)), \(a_{n} \ge 0\) (\(n \in \mathrm{N} = \{ 1,2,\ldots \} \)), such that
$$\begin{aligned}& 0 < \int _{0}^{\infty } x^{p[1 - (\frac{\lambda - \sigma }{p} + \frac{ \mu }{q})] - 1} f^{p}(x) \,dx < \infty \quad \text{and}\quad 0 < \sum_{n = 1}^{\infty } n ^{q[1 - (\frac{\sigma }{p} + \frac{\lambda - \mu }{q})] - 1} a_{n} ^{q} < \infty . \end{aligned}$$

Lemma 1

Define the following weight function:
$$ \varpi (\sigma ,x): = x^{\lambda - \sigma } \sum_{n = 1}^{\infty } \frac{n ^{\sigma - 1}}{(x + n)^{\lambda }}\quad (x \in \mathrm{R}_{ +} ). $$
(4)
We have the following inequality:
$$ \varpi (\sigma ,x) < B(\sigma ,\lambda - \sigma )\quad (x \in \mathrm{R} _{ +} ). $$
(5)

Proof

For fixed \(x > 0\), we set the function \(g_{x}(t): = \frac{t ^{\sigma - 1}}{(x + t)^{\lambda }}\) (\(t > 0\)). Using the Euler–Maclaurin summation formula (cf. [20]), for \(\rho (t): = t - [t] - \frac{1}{2}\), we have
$$\begin{aligned}& \sum_{n = 1}^{\infty } g_{x}(n) = \int _{1}^{\infty } g_{x}(t)\,dt + \frac{1}{2} g_{x}(1) + \int _{1}^{\infty } \rho (t)g'{}_{x}(t) \,dt = \int _{0}^{\infty } g_{x}(t)\,dt - h(x), \\& h(x): = \int _{0}^{1} g_{x}(t)\,dt - \frac{1}{2}g_{x}(1) - \int _{1}^{ \infty } \rho (t)g'_{x}(t) \,dt. \end{aligned}$$
We obtain \(- \frac{1}{2}g_{x}(1) = \frac{ - 1}{2(x + 1)^{\lambda }} \),
$$\begin{aligned}& \begin{aligned} \int _{0}^{1} g_{x}(t)\,dt &= \int _{0}^{1} \frac{t^{\sigma - 1}}{(x + t)^{ \lambda }} \,dt = \frac{1}{\sigma } \int _{0}^{1} \frac{dt^{\sigma }}{(x + t)^{\lambda }} = \frac{1}{\sigma } \frac{t^{\sigma }}{(x + t)^{ \lambda }} \bigg\vert _{0}^{1} + \frac{\lambda }{\sigma } \int _{0}^{1} \frac{t ^{\sigma } \,dt}{(x + t)^{\lambda + 1}} \\ &= \frac{1}{\sigma } \frac{1}{(x + 1)^{\lambda }} + \frac{\lambda }{ \sigma (\sigma + 1)} \int _{0}^{1} \frac{dt^{\sigma + 1}}{(x + t)^{ \lambda + 1}} \\ &> \frac{1}{\sigma } \frac{1}{(x + 1)^{\lambda }} + \frac{\lambda }{ \sigma (\sigma + 1)}\biggl[ \frac{t^{\sigma + 1}}{(x + t)^{\lambda + 1}}\biggr]_{0} ^{1} + \frac{\lambda (\lambda + 1)}{\sigma (\sigma + 1)(x + 1)^{ \lambda + 2}} \int _{0}^{1} t^{\sigma + 1} \,dt \\ &= \frac{1}{\sigma } \frac{1}{(x + 1)^{\lambda }} + \frac{\lambda }{ \sigma (\sigma + 1)}\frac{1}{(x + 1)^{\lambda + 1}} + \frac{\lambda ( \lambda + 1)}{\sigma (\sigma + 1)(\sigma + 2)}\frac{1}{(x + 1)^{ \lambda + 2}}, \end{aligned} \\& \begin{aligned} - g'_{x}(t) &= - \frac{(\sigma - 1)t^{\sigma - 2}}{(x + t)^{\lambda }} + \frac{\lambda t^{\sigma - 1}}{(x + t)^{\lambda + 1}} = \frac{(1 - \sigma )t^{\sigma - 2}}{(x + t)^{\lambda }} + \frac{\lambda t^{\sigma - 2}}{(x + t)^{\lambda }} - \frac{\lambda xt^{\sigma - 2}}{(x + t)^{ \lambda + 1}} \\ &= \frac{(\lambda + 1 - \sigma )t^{\sigma - 2}}{(x + t)^{\lambda }} - \frac{ \lambda xt^{\sigma - 2}}{(x + t)^{\lambda + 1}}. \end{aligned} \end{aligned}$$
For \(0 < \sigma \le 2\), \(\sigma < \lambda \le 28\), we find \(\lambda + 1 - \sigma > 0\),
$$ ( - 1)^{i}\frac{d^{i}}{dt^{i}}\biggl[\frac{t^{\sigma - 2}}{(x + t)^{\lambda }} \biggr] > 0,\quad\quad ( - 1)^{i}\frac{d^{i}}{dt^{i}}\biggl[\frac{t^{\sigma - 2}}{(x + t)^{ \lambda + 1}}\biggr] > 0 \quad (i = 0,1,2,3), $$
and then, by the Euler–Maclaurin summation formula (cf. [20]), we find
$$\begin{aligned}& (\lambda + 1 - \sigma ) \int _{1}^{\infty } \rho (t)\frac{t^{\sigma - 2}}{(x + t)^{\lambda }} \,dt \\& \quad > - \frac{\lambda + 1 - \sigma }{12(x + 1)^{ \lambda }}, \\& \quad \quad{} - x\lambda \int _{1}^{\infty } \rho (t)\frac{t^{\sigma - 2}}{(x + t)^{ \lambda + 1}} \,dt > \frac{x\lambda }{12(x + 1)^{\lambda + 1}} - \frac{x \lambda }{720}\biggl[\frac{t^{\sigma - 2}}{(x + t)^{\lambda + 1}} \biggr]''_{t = 1} \\& \quad > \frac{(x + 1)\lambda - \lambda }{12(x + 1)^{\lambda + 1}} - \frac{(x + 1)\lambda }{720}\biggl[\frac{(\lambda + 1)(\lambda + 2)}{(x + 1)^{\lambda + 3}} + \frac{2(\lambda + 1)(2 - \sigma )}{(x + 1)^{\lambda + 2}} + \frac{(2 - \sigma )(3 - \sigma )}{(x + 1)^{\lambda + 1}}\biggr] \\& \quad = \frac{\lambda }{12(x + 1)^{\lambda }} - \frac{\lambda }{12(x + 1)^{ \lambda + 1}} \\& \quad\quad{} - \frac{\lambda }{720}\biggl[ \frac{(\lambda + 1)(\lambda + 2)}{(x + 1)^{\lambda + 2}} + \frac{2(\lambda + 1)(2 - \sigma )}{(x + 1)^{ \lambda + 1}} + \frac{(2 - \sigma )(3 - \sigma )}{(x + 1)^{\lambda }} \biggr]. \end{aligned}$$
Hence, we have \(h(x) > \frac{h_{1}}{(x + 1)^{\lambda }} + \frac{\lambda h_{2}}{(x + 1)^{\lambda + 1}} + \frac{\lambda (\lambda + 1)h_{3}}{(x + 1)^{\lambda + 2}}\), where
$$ h_{1}: = \frac{1}{\sigma } - \frac{1}{2} - \frac{1 - \sigma }{12} - \frac{ \lambda (2 - \sigma )(3 - \sigma )}{720},\quad\quad h_{2}: = \frac{1}{\sigma ( \sigma + 1)} - \frac{1}{12} - \frac{(\lambda + 1)(2 - \sigma )}{720}, $$
and \(h_{3}: = \frac{1}{\sigma (\sigma + 1)(\sigma + 2)} - \frac{\lambda + 2}{720}\).
For \(\lambda \in (0,28]\), \(\frac{\lambda }{720} < \frac{1}{24}\), \(\sigma \in (0,2]\), it follows that
$$ h_{1} > \frac{1}{\sigma } - \frac{1}{2} - \frac{1 - \sigma }{12} - \frac{(2 - \sigma )(3 - \sigma )}{24} = \frac{24 - 20\sigma + 7\sigma ^{2} - \sigma ^{3}}{24\sigma } > 0. $$
In fact, setting \(g(\sigma ): = 24 - 20\sigma + 7\sigma ^{2} - \sigma ^{3}\) (\(\sigma \in (0,2]\)), we obtain
$$ g'(\sigma ) = - 20 + 14\sigma ^{2} - 3\sigma ^{2} = - 3\biggl(\sigma - \frac{7}{3}\biggr)^{2} - \frac{11}{3} < 0, $$
and then
$$ h_{1} > \frac{g(\sigma )}{24\sigma } \ge \frac{g(2)}{24\sigma } = \frac{4}{24 \sigma } > 0\quad \big(\sigma \in (0,2]\big). $$
We still find that \(h_{2} > \frac{1}{6} - \frac{1}{12} - \frac{30}{360} = 0\), and \(h_{3} \ge \frac{1}{24} - \frac{30}{720} = 0\). Hence, we find \(h(x) > 0\), and then
$$\begin{aligned} \begin{aligned} x^{\lambda - \sigma } \sum_{n = 1}^{\infty } g_{x}(n)& < x^{\lambda - \sigma } \int _{0}^{\infty } g_{x}(t)\,dt \\ &= x^{\lambda - \sigma } \int _{0}^{\infty } \frac{t^{\sigma - 1}\,dt}{(x + t)^{\lambda }} = \int _{0}^{\infty } \frac{u^{\sigma - 1}\,du}{(1 + u)^{ \lambda }} = B(\sigma , \lambda - \sigma ), \end{aligned} \end{aligned}$$
namely, (5) follows. □

Lemma 2

We have the following reverse inequality:
$$\begin{aligned}& \begin{aligned}[b] I &= \int _{0}^{\infty } \sum_{n = 1}^{\infty } \frac{f(x)a_{n}}{(x + n)^{ \lambda }} \,dx \\&> B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{ \frac{1}{q}}(\mu ,\lambda - \mu ) \\ &\quad{} \times \biggl\{ \int _{0}^{\infty } x^{p[1 - (\frac{\lambda - \sigma }{p} + \frac{ \mu }{q})] - 1} f^{p}(x) \,dx\biggr\} ^{\frac{1}{p}}\Biggl\{ \sum_{n = 1}^{\infty } n ^{q[1 - (\frac{\sigma }{p} + \frac{\lambda - \mu }{q})] - 1} a_{n} ^{q}\Biggr\} ^{\frac{1}{q}}. \end{aligned} \end{aligned}$$
(6)

Proof

For \(n \in \mathbf{N}\), setting \(x = nu\), we obtain another weight function:
$$ \omega (\mu ,n): = n^{\lambda - \mu } \int _{0}^{\infty } \frac{x^{ \mu - 1}\,dx}{(x + n)^{\lambda }} = \int _{0}^{\infty } \frac{u^{\mu - 1}\,du}{(u + 1)^{\lambda }} = B(\mu ,\lambda - \mu ). $$
(7)
For \(p < 0\), \(0 < q < 1\), by the reverse Hölder inequality (cf. [27]) and Lebesgue term by term integration theorem (cf. [28]), we obtain
$$\begin{aligned} \int _{0}^{\infty } \sum_{n = 1}^{\infty } \frac{f(x)a_{n}}{(x + n)^{ \lambda }} \,dx &= \int _{0}^{\infty } \sum_{n = 1}^{\infty } \frac{1}{(x + n)^{\lambda }} \biggl[\frac{n^{(\sigma - 1)/p}}{x^{(\mu - 1)/q}}f(x)\biggr] \biggl[ \frac{x ^{(\mu - 1)/q}}{n^{(\sigma - 1)/p}}a_{n}\biggr]\,dx \\ &\ge \Biggl\{ \int _{0}^{\infty } \Biggl[\sum _{n = 1}^{\infty } \frac{1}{(x + n)^{ \lambda }} \frac{n^{\sigma - 1}}{x^{(\mu - 1)(p - 1)}} \Biggr]f^{p}(x)\,dx\Biggr\} ^{\frac{1}{p}} \\ &\quad{}\times \Biggl\{ \sum _{n = 1}^{\infty } \biggl[ \int _{0}^{\infty } \frac{1}{(x + n)^{\lambda }} \frac{x^{\mu - 1}}{n^{(\sigma - 1)(q - 1)}} \,dx\biggr]a_{n} ^{q}\Biggr\} ^{\frac{1}{q}} \\ &= \biggl\{ \int _{0}^{\infty } \varpi (\sigma ,x) x^{p[1 - (\frac{\lambda - \sigma }{p} + \frac{\mu }{q})] - 1}f^{p}(x)\,dx\biggr\} ^{\frac{1}{p}} \\ &\quad{}\times\Biggl\{ \sum _{n = 1}^{\infty } \omega (\mu ,n) n^{q[1 - (\frac{\sigma }{p} + \frac{ \lambda - \mu }{q})] - 1}a_{n}^{q}\Biggr\} ^{\frac{1}{q}}. \end{aligned}$$
Then, by (5) and (7), we have (6). □

Remark 1

For \(\mu + \sigma = \lambda \), we find
$$\begin{aligned}& \varpi (\sigma ,x) = x^{\mu } \sum_{n = 1}^{\infty } \frac{n^{\sigma - 1}}{(x + n)^{\lambda }} \quad (x \in \mathrm{R}_{ +} ), \\& 0 < \int _{0}^{\infty } x^{p(1 - \mu ) - 1} f^{p}(x) \,dx < \infty \quad \text{and}\quad 0 < \sum_{n = 1}^{\infty } n^{q(1 - \sigma ) - 1} a_{n}^{q} < \infty , \end{aligned}$$
and then we reduce (6) as follows:
$$ \int _{0}^{\infty } \sum_{n = 1}^{\infty } \frac{f(x)a_{n}}{(x + n)^{ \lambda }} \,dx > B(\mu ,\sigma )\biggl[ \int _{0}^{\infty } x^{p(1 - \mu ) - 1} f^{p}(x) \,dx\biggr]^{\frac{1}{p}}\Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \sigma ) - 1} a_{n}^{q}\Biggr]^{\frac{1}{q}}. $$
(8)

Lemma 3

The constant factor\(B(\mu ,\sigma )\)in (8) is the best possible.

Proof

For \(0 < \varepsilon < q\sigma \), we set
$$ \tilde{f}(x): = \textstyle\begin{cases} 0,&0 < x < 1, \\ x^{\mu - \frac{\varepsilon }{p} - 1},&x \ge 1, \end{cases}\displaystyle \quad\quad \tilde{a}_{n}: = n^{\sigma - \frac{\varepsilon }{q} - 1}\quad (n \in \mathrm{N}). $$
If there exists a positive constant M (\(M \ge B(\mu ,\sigma )\)), such that (8) is valid when replacing \(B(\mu ,\sigma )\) by M, then by substitution of \(f(x) = \tilde{f}(x)\), \(a_{n} = \tilde{a}_{n}\), we have
$$\begin{aligned} \tilde{I}: = {}& \int _{0}^{\infty } \sum_{n = 1}^{\infty } \frac{ \tilde{f}(x)\tilde{a}_{n}}{(x + n)^{\lambda }} \,dx > M\biggl[ \int _{0}^{ \infty } x^{p(1 - \mu ) - 1} \tilde{f}^{p}(x)\,dx\biggr]^{\frac{1}{p}}\Biggl[ \sum _{n = 1}^{\infty } n^{q(1 - \sigma ) - 1} \tilde{a}_{n}^{q} \Biggr]^{ \frac{1}{q}} \\ ={}& M\biggl( \int _{1}^{\infty } x^{ - \varepsilon - 1} \,dx \biggr)^{\frac{1}{p}}\Biggl( \sum_{n = 1}^{\infty } n^{ - \varepsilon - 1} \Biggr)^{\frac{1}{q}} \\ \ge {}&M\biggl( \int _{1}^{\infty } x^{ - \varepsilon - 1} \,dx \biggr)^{\frac{1}{p}}\biggl( \int _{1}^{\infty } x^{ - \varepsilon - 1}\,dx \biggr)^{\frac{1}{q}} = M \int _{1} ^{\infty } x^{ - \varepsilon - 1}\,dx = \frac{M}{\varepsilon }. \end{aligned}$$
For \(0 < \sigma - \frac{\varepsilon }{q} < 2\) (\(0 < q < 1\)), by (5), we obtain
$$\begin{aligned} \tilde{I} &= \int _{1}^{\infty } \Biggl[x^{(\mu + \frac{\varepsilon }{q})} \sum _{n = 1}^{\infty } \frac{n^{(\sigma - \frac{\varepsilon }{q}) - 1}}{(x + n)^{\lambda }} \Biggr]x^{ - \varepsilon - 1} \,dx = \int _{1}^{\infty } \varpi \biggl(\sigma - \frac{\varepsilon }{q},x\biggr) x^{ - \varepsilon - 1}\,dx \\ &\le B\biggl(\mu + \frac{\varepsilon }{q},\sigma - \frac{\varepsilon }{q}\biggr) \int _{1}^{\infty } x^{ - \varepsilon - 1} \,dx = \frac{1}{\varepsilon } B\biggl(\mu + \frac{\varepsilon }{q},\sigma - \frac{\varepsilon }{q} \biggr). \end{aligned}$$
Then we have
$$ B\biggl(\mu + \frac{\varepsilon }{q},\sigma - \frac{\varepsilon }{q}\biggr) \ge \varepsilon \tilde{I} \ge M. $$
For \(\varepsilon \to 0^{ +} \), in view of the continuity of the beta function, it follows that \(B(\mu ,\sigma ) \ge M\). Therefore, \(M = B(\mu ,\sigma )\) is the best possible constant factor of (8). □

Remark 2

Setting \(\hat{\mu }: = \frac{\lambda - \sigma }{p} + \frac{\mu }{q}\), \(\hat{\sigma }: = \frac{\sigma }{p} + \frac{\lambda - \mu }{q}\), we have
$$ \hat{\mu } + \hat{\sigma } = \frac{\lambda - \sigma }{p} + \frac{ \mu }{q} + \frac{\sigma }{p} + \frac{\lambda - \mu }{q} = \frac{ \lambda }{p} + \frac{\lambda }{q} = \lambda . $$
And, for \(\lambda - \mu - \sigma \in ( - q\sigma ,q(\lambda - \sigma ))\), we find
$$ \begin{gathered} \hat{\mu } > \frac{\lambda - \sigma }{p} + \frac{(1 - q)(\lambda - \sigma )}{q} = 0,\quad\quad \hat{\mu } < \frac{\lambda - \sigma }{p} + \frac{ \lambda - \sigma + q\sigma }{q} = \lambda , \\ 0 < \hat{\sigma } = \lambda - \hat{\mu } < \lambda ,\quad\quad B(\hat{\mu }, \hat{\sigma } ) \in \mathrm{R}_{ +}. \end{gathered} $$
We can reduce (6) as follows:
$$\begin{aligned}& \begin{aligned}[b] \int _{0}^{\infty } \sum_{n = 1}^{\infty } \frac{f(x)a_{n}}{(x + n)^{ \lambda }} \,dx &> B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{ \frac{1}{q}}(\mu ,\lambda - \mu ) \\ &\quad{} \times \biggl[ \int _{0}^{\infty } x^{p(1 - \hat{\mu } ) - 1} f^{p}(x) \,dx\biggr]^{ \frac{1}{p}}\Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \hat{\sigma } ) - 1} a _{n}^{q}\Biggr]^{\frac{1}{q}}. \end{aligned} \end{aligned}$$
(9)

Lemma 4

If\(\lambda - \mu - \sigma \in ( - q\sigma ,q(\lambda - \sigma ))\), the constant factor\(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu ,\lambda - \mu )\)in (9) is the best possible, then we have\(\lambda - \mu - \sigma = 0\), namely, \(\mu + \sigma = \lambda \).

Proof

If the constant factor \(B^{\frac{1}{p}}(\sigma , \lambda - \sigma )B^{\frac{1}{q}}(\mu ,\lambda - \mu )\) in (9) is the best possible, then, by (8), the unique best possible constant factor must be \(B(\hat{\mu },\hat{\sigma } )\) (\(\in \mathrm{R}_{ +} \)), namely,
$$ B(\hat{\mu },\hat{\sigma } ) =B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu ,\lambda - \mu ). $$
By the reverse Hölder inequality (cf. [27]), we find
$$\begin{aligned}& \begin{aligned}[b] B(\hat{\mu },\hat{\sigma } ) &= \int _{0}^{\infty } \frac{t^{\hat{\mu } - 1}}{(1 + t)^{\lambda }} \,dt = \int _{0}^{\infty } \frac{t^{\frac{ \lambda - \sigma }{p} + \frac{\mu }{q} - 1}}{(1 + t)^{\lambda }} \,dt = \int _{0}^{\infty } \frac{1}{(1 + t)^{\lambda }} \bigl(t^{\frac{\lambda - \sigma - 1}{p}}\bigr) \bigl(t^{\frac{\mu - 1}{q}}\bigr) \,dt \\ &\ge \biggl[ \int _{0}^{\infty } \frac{1}{(1 + t)^{\lambda }} t^{\lambda - \sigma - 1} \,dt\biggr]{}^{\frac{1}{p}}\biggl[ \int _{0}^{\infty } \frac{1}{(1 + t)^{ \lambda }} t^{\mu - 1} \,dt\biggr]{}^{\frac{1}{q}} \\ &= B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu , \lambda - \mu ). \end{aligned} \end{aligned}$$
(10)
We observe that (10) keeps the form of an equality if and only if there exist constants A, B, such that they are not all zero and \(At^{\lambda - \sigma - 1} = Bt^{\mu - 1}\)a.e. in\(\mathrm{R}_{ +}\). Suppose that \(A \ne 0\). We find that
$$ t^{\lambda - \mu - \sigma } = \frac{B}{A}\quad \textit{a.e.in }\mathrm{R}_{ +}, $$
and then \(\lambda - \mu - \sigma = 0\), namely, \(\mu + \sigma = \lambda\). □

3 Main results

Theorem 1

Inequality (6) is equivalent to the following inequalities:
$$\begin{aligned}& \begin{aligned}[b] J_{1}: = {}&\Biggl\{ \sum _{n = 1}^{\infty } n^{p(\frac{\sigma }{p} + \frac{ \lambda - \mu }{q}) - 1} \biggl[ \int _{0}^{\infty } \frac{f(x)}{(x + n)^{ \lambda }} \,dx \biggr]^{p}\Biggr\} ^{\frac{1}{p}} \\ >{}& B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu , \lambda - \mu )\biggl\{ \int _{0}^{\infty } x^{p[1 - (\frac{\lambda - \sigma }{p} + \frac{\mu }{q})] - 1} f^{p}(x) \,dx\biggr\} ^{\frac{1}{p}}, \end{aligned} \end{aligned}$$
(11)
$$\begin{aligned}& \begin{aligned}[b] J_{2}: = {}&\Biggl\{ \int _{0}^{\infty } x^{q(\frac{\lambda - \sigma }{p} + \frac{ \mu }{q}) - 1}\Biggl[\sum _{n = 1}^{\infty } \frac{a_{n}}{(x + n)^{\lambda }} \Biggr]^{q} \,dx\Biggr\} ^{\frac{1}{q}} \\ >{}& B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu , \lambda - \mu )\Biggl\{ \sum_{n = 1}^{\infty } n^{q[1 - (\frac{\sigma }{p} + \frac{\lambda - \mu }{q})] - 1} a_{n}^{q}\Biggr\} ^{\frac{1}{q}}. \end{aligned} \end{aligned}$$
(12)

If the constant factor\(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B ^{\frac{1}{q}}(\mu ,\lambda - \mu )\)in (6) is the best possible, then so is the constant factor in (11) and (12).

In particular, for\(\mu + \sigma = \lambda \)in (6), (11) and (12), we have (8) and the following equivalent reverse inequalities with the best possible constant factor\(B(\mu ,\sigma )\):
$$\begin{aligned}& \Biggl\{ \sum_{n = 1}^{\infty } n^{p\sigma - 1} \biggl[ \int _{0}^{\infty } \frac{f(x)}{(x + n)^{\lambda }} \,dx \biggr]^{p}\Biggr\} ^{\frac{1}{p}}> B(\mu , \sigma )\biggl[ \int _{0}^{\infty } x^{p(1 - \mu ) - 1} f^{p}(x) \,dx\biggr]^{ \frac{1}{p}}, \end{aligned}$$
(13)
$$\begin{aligned}& \Biggl\{ \int _{0}^{\infty } x^{q\mu - 1}\Biggl[\sum _{n = 1}^{\infty } \frac{a_{n}}{(x + n)^{\lambda }} \Biggr]^{q} \,dx\Biggr\} ^{\frac{1}{q}}> B(\mu , \sigma )\Biggl[\sum _{n = 1}^{\infty } n^{q(1 - \sigma ) - 1} a_{n}^{q} \Biggr]^{ \frac{1}{q}}. \end{aligned}$$
(14)

Proof

Suppose that (11) is valid. By Lebesgue term by term integration theorem and the reverse Hölder inequality (cf. [27, 28]), we have
$$\begin{aligned}& \begin{aligned}[b] I&= \sum_{n = 1}^{\infty } \int _{0}^{\infty } \frac{f(x)a_{n}}{(x + n)^{ \lambda }} \,dx = \sum _{n = 1}^{\infty } \biggl[n^{\frac{ - 1}{p} + (\frac{ \sigma }{p} + \frac{\lambda - \mu }{q})} \int _{0}^{\infty } \frac{f(x)}{(x + n)^{\lambda }} \,dx\biggr] \bigl[n^{\frac{1}{p} - ( \frac{\sigma }{p} + \frac{\lambda - \mu }{q})}a_{n}\bigr] \\ &\ge J_{1}\Biggl\{ \sum_{n = 1}^{\infty } n^{q[1 - (\frac{\sigma }{p} + \frac{ \lambda - \mu }{q})] - 1} a_{n}^{q}\Biggr\} ^{\frac{1}{q}}. \end{aligned} \end{aligned}$$
(15)
Then, by (11), we have (6). On the other hand, assuming that (6) is valid, we set
$$ a_{n}: = n^{p(\frac{\sigma }{p} + \frac{\lambda - \mu }{q}) - 1}\biggl[ \int _{0}^{\infty } \frac{f(x)}{(x + n)^{\lambda }} \,dx \biggr]^{p - 1},\quad n \in \mathrm{N}. $$
If \(J_{1} = \infty \), then (11) is naturally valid; if \(J_{1} = 0\), then it is impossible to make (11) valid, namely \(J_{1} > 0\). Suppose that \(0 < J_{1} < \infty \). By (6), we have
$$\begin{aligned}& \begin{aligned} \sum_{n = 1}^{\infty } n^{q[1 - (\frac{\sigma }{p} + \frac{\lambda - \mu }{q})] - 1} a_{n}^{q} &= J_{1}^{p} = I\\&> B^{\frac{1}{p}}(\sigma , \lambda - \sigma )B^{\frac{1}{q}}(\mu ,\lambda - \mu ) \\ &\quad{} \times \biggl\{ \int _{0}^{\infty } x^{p[1 - (\frac{\lambda - \sigma }{p} + \frac{ \mu }{q})] - 1} f^{p}(x) \,dx\biggr\} ^{\frac{1}{p}}\Biggl\{ \sum_{n = 1}^{\infty } n ^{q[1 - (\frac{\sigma }{p} + \frac{\lambda - \mu }{q})] - 1} a_{n} ^{q}\Biggr\} ^{\frac{1}{q}}, \end{aligned} \\& \begin{aligned} \Biggl\{ \sum_{n = 1}^{\infty } n^{q[1 - (\frac{\sigma }{p} + \frac{\lambda - \mu }{q})] - 1} a_{n}^{q}\Biggr\} ^{\frac{1}{p}} = J_{1}&> B^{\frac{1}{p}}( \sigma ,\lambda - \sigma )B^{\frac{1}{q}}( \mu ,\lambda - \mu ) \\ &\quad{} \times \biggl\{ \int _{0}^{\infty } x^{p[1 - (\frac{\lambda - \sigma }{p} + \frac{ \mu }{q})] - 1} f^{p}(x) \,dx\biggr\} ^{\frac{1}{p}}, \end{aligned} \end{aligned}$$
namely, (11) follows, which is equivalent to (6).
Suppose that (12) is valid. By the reverse Hölder inequality, we have
$$\begin{aligned}& \begin{aligned}[b] I&= \int _{0}^{\infty } \bigl[x^{\frac{1}{q} - (\frac{\lambda - \sigma }{p} + \frac{\mu }{q})}f(x)\bigr] \Biggl[x^{\frac{ - 1}{q} + ( \frac{\lambda - \sigma }{p} + \frac{\mu }{q})}\sum_{n = 1}^{\infty } \frac{a _{n}}{(x + n)^{\lambda }} \Biggr]\,dx \\ &\ge \biggl\{ \int _{0}^{\infty } x^{p\{ 1 - (\frac{\lambda - \sigma }{p} + \frac{ \mu }{q})] - 1}f^{p}(x) \,dx\biggr\} ^{\frac{1}{p}}J_{2}. \end{aligned} \end{aligned}$$
(16)
Then, by (12), we have (6). On the other hand, assuming that (6) is valid, we set
$$ f(x): = x^{q(\frac{\lambda - \sigma }{p} + \frac{\mu }{q}) - 1}\Biggl[ \sum_{n = 1}^{\infty } \frac{a_{n}}{(x + n)^{\lambda }} \Biggr]^{q - 1},\quad x \in \mathrm{R}_{ +}. $$
If \(J_{2} = \infty \), then (12) is naturally valid; if \(J_{2} = 0\), then it is impossible to make (12) valid, namely \(J_{2} > 0\). Suppose that \(0 < J_{2} < \infty \). By (6), we have
$$\begin{aligned}& \begin{aligned} & \int _{0}^{\infty } x^{p[1 - (\frac{\lambda - \sigma }{p} + \frac{ \mu }{q})] - 1} f^{p}(x) \,dx \\ &\quad = J_{2}^{q} = I\\ &\quad > B^{\frac{1}{p}}(\sigma , \lambda - \sigma )B^{\frac{1}{q}}(\mu ,\lambda - \mu ) \\ &\quad \quad{} \times \biggl\{ \int _{0}^{\infty } x^{p[1 - (\frac{\lambda - \sigma }{p} + \frac{ \mu }{q})] - 1} f^{p}(x) \,dx\biggr\} ^{\frac{1}{p}}\Biggl\{ \sum_{n = 1}^{\infty } n ^{q[1 - (\frac{\sigma }{p} + \frac{\lambda - \mu }{q})] - 1} a_{n} ^{q}\Biggr\} ^{\frac{1}{q}}, \end{aligned} \\ & \begin{aligned} \biggl\{ \int _{0}^{\infty } x^{p[1 - (\frac{\lambda - \sigma }{p} + \frac{ \mu }{q})] - 1} f^{p}(x) \,dx\biggr\} ^{\frac{1}{q}} = J_{2}&> B^{\frac{1}{p}}( \sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu ,\lambda - \mu ) \\ &\quad{} \times \Biggl\{ \sum_{n = 1}^{\infty } n^{q[1 - (\frac{\sigma }{p} + \frac{ \lambda - \mu }{q})] - 1} a_{n}^{q}\Biggr\} ^{\frac{1}{q}}, \end{aligned} \end{aligned}$$
namely, (12) follows, which is equivalent to (6).

Hence, inequalities (6), (11) and (12) are equivalent.

If the constant factor \(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B ^{\frac{1}{q}}(\mu ,\lambda - \mu )\) in (6) is the best possible, then so is the constant factor in (11) and (12). Otherwise, by (15) (or (16)), we would reach the contradiction that the constant factor in (6) is not the best possible. □

Theorem 2

The following statements (i), (ii), (iii) and (iv) are equivalent:
  1. (i)

    \(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}( \mu ,\lambda - \mu )\)is independent ofp, q;

     
  2. (ii)

    \(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}( \mu ,\lambda - \mu )\)is expressible as a single integral;

     
  3. (iii)

    \(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{ \frac{1}{q}}(\mu ,\lambda - \mu )\)is the best possible of (6);

     
  4. (iv)

    If\(\lambda - \mu - \sigma \in ( - q\sigma ,q(\lambda - \sigma ))\), then\(\mu + \sigma = \lambda \).

     

Proof

(i)⇒(ii). In view of \(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu ,\lambda - \mu )\) is independent of p, q, we find
$$ \begin{gathered} B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu ,\lambda - \mu ) \\ \quad = \lim_{ \substack{p \to - \infty , \\q \to 1^{ +}}} B ^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu ,\lambda - \mu ) = B(\mu ,\lambda - \mu ), \end{gathered} $$
which is a single integral \(\int _{0}^{\infty } \frac{t^{\mu - 1}}{(1 + t)^{\lambda }} \,dt\).

(ii)⇒(iv). Suppose that \(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B ^{\frac{1}{q}}(\mu ,\lambda - \mu )\) is expressible as a single integral \(\int _{0}^{\infty } \frac{t^{\frac{\lambda - \sigma }{p} + \frac{ \mu }{q} - 1}}{(1 + t)^{\lambda }} \,dt\). Then (10) keeps the form of equality. By the proof of Lemma 4, for \(\lambda - \mu - \sigma \in ( - q\sigma ,q(\lambda - \sigma ))\), we have \(\mu + \sigma = \lambda \).

(iv)⇒(i). If \(\mu + \sigma = \lambda \), then
$$ B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu ,\lambda - \mu ) = B(\mu ,\sigma ), $$
which is independent of pq.

Hence, we have (i)⇔(ii)⇔(iv).

(i)⇒(iii). By Lemma 3, for \(\mu + \sigma = \lambda \), \(B^{ \frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu ,\lambda - \mu )\) is the best possible of (6).

(iii)⇒(iv). By Lemma 4, we have \(\mu + \sigma = \lambda \).

Therefore, we show that (iv)⇔(iii), and then the statements (i), (ii), (iii) and (iv) are equivalent. □

4 Two corollaries and some particular inequalities

Replacing x by \(\frac{1}{x}\), and then setting \(F(x) = x^{\lambda - 2}f( \frac{1}{x})\) in Theorem 1 and then Theorem 2, we have the following.

Corollary 1

If\(F(x)\), \(a_{n} \ge 0\), such that
$$ 0 < \int _{0}^{\infty } x^{p[1 - (\frac{\sigma }{p} + \frac{\lambda - \mu }{q})] - 1} F^{p}(x) \,dx < \infty \quad \textit{and}\quad 0 < \sum_{n = 1}^{\infty } n ^{q[1 - (\frac{\sigma }{p} + \frac{\lambda - \mu }{q})] - 1} a_{n} ^{q} < \infty , $$
then the following inequalities are equivalent:
$$\begin{aligned}& \begin{aligned}[b] & \int _{0}^{\infty } \sum_{n = 1}^{\infty } \frac{F(x)a_{n}}{(1 + xn)^{ \lambda }} \,dx \\ &\quad > B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{ \frac{1}{q}}(\mu ,\lambda - \mu ) \\ &\quad \quad{} \times \biggl\{ \int _{0}^{\infty } x^{p[1 - (\frac{\sigma }{p} + \frac{ \lambda - \mu }{q})] - 1} F^{p}(x) \,dx\biggr\} ^{\frac{1}{p}}\Biggl\{ \sum_{n = 1} ^{\infty } n^{q[1 - (\frac{\sigma }{p} + \frac{\lambda - \mu }{q})] - 1} a_{n}^{q}\Biggr\} ^{\frac{1}{q}}, \end{aligned} \end{aligned}$$
(17)
$$\begin{aligned}& \begin{aligned}[b] &\Biggl\{ \sum_{n = 1}^{\infty } n^{p(\frac{\sigma }{p} + \frac{\lambda - \mu }{q}) - 1} \biggl[ \int _{0}^{\infty } \frac{F(x)}{(1 + xn)^{\lambda }} \,dx \biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\ &\quad > B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu , \lambda - \mu )\biggl\{ \int _{0}^{\infty } x^{p[1 - (\frac{\sigma }{p} + \frac{ \lambda - \mu }{q})] - 1} F^{p}(x) \,dx\biggr\} ^{\frac{1}{p}}, \end{aligned} \end{aligned}$$
(18)
$$\begin{aligned}& \begin{aligned}[b] &\Biggl\{ \int _{0}^{\infty } x^{q(\frac{\sigma }{p} + \frac{\lambda - \mu }{q}) - 1}\Biggl[\sum _{n = 1}^{\infty } \frac{a_{n}}{(1 + xn)^{\lambda }} \Biggr]^{q} \,dx\Biggr\} ^{\frac{1}{q}} \\ &\quad > B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu , \lambda - \mu )\Biggl\{ \sum_{n = 1}^{\infty } n^{q[1 - (\frac{\sigma }{p} + \frac{\lambda - \mu }{q})] - 1} a_{n}^{q}\Biggr\} ^{\frac{1}{q}}. \end{aligned} \end{aligned}$$
(19)
If the constant factor\(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B ^{\frac{1}{q}}(\mu ,\lambda - \mu )\)in (17) is the best possible, then so is the constant factor in (18) and (19). In particular, for\(\mu = \lambda - \sigma \)in (17), (18) and (19), we have the following equivalent inequalities with the best possible constant factor\(B( \lambda - \sigma ,\sigma )\):
$$\begin{aligned}& \begin{aligned}[b] \int _{0}^{\infty } \sum_{n = 1}^{\infty } \frac{F(x)a_{n}}{(1 + xn)^{ \lambda }} \,dx &> B(\lambda - \sigma ,\sigma ) \\ &\quad{} \times \biggl[ \int _{0}^{\infty } x^{p(1 - \sigma ) - 1} F^{p}(x) \,dx\biggr]^{ \frac{1}{p}}\Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \sigma ) - 1} a_{n}^{q}\Biggr]^{ \frac{1}{q}}, \end{aligned} \end{aligned}$$
(20)
$$\begin{aligned}& \Biggl\{ \sum_{n = 1}^{\infty } n^{p\sigma - 1} \biggl[ \int _{0}^{\infty } \frac{F(x)}{(1 + xn)^{\lambda }} \,dx \biggr]^{p}\Biggr\} ^{\frac{1}{p}}> B(\lambda - \sigma ,\sigma )\biggl[ \int _{0}^{\infty } x^{p(1 - \sigma ) - 1} F^{p}(x) \,dx\biggr]^{ \frac{1}{p}}, \end{aligned}$$
(21)
$$\begin{aligned}& \Biggl\{ \int _{0}^{\infty } x^{q\sigma - 1}\Biggl[\sum _{n = 1}^{\infty } \frac{a _{n}}{(1 + xn)^{\lambda }} \Biggr]^{q} \,dx\Biggr\} ^{\frac{1}{q}}> B(\lambda - \sigma ,\sigma )\Biggl[\sum _{n = 1}^{\infty } n^{q(1 - \sigma ) - 1} a_{n} ^{q}\Biggr]^{\frac{1}{q}}. \end{aligned}$$
(22)

Corollary 2

The following statements (I), (II), (III) and (IV) are equivalent:
  1. (I)

    \(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu , \lambda - \mu )\)is independent ofp, q;

     
  2. (II)

    \(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}(\mu , \lambda - \mu )\)is expressible as a single integral;

     
  3. (III)

    \(B^{\frac{1}{p}}(\sigma ,\lambda - \sigma )B^{\frac{1}{q}}( \mu ,\lambda - \mu )\)is the best possible of (17);

     
  4. (IV)

    If\(\lambda - \mu - \sigma \in ( - q\sigma ,q(\lambda - \sigma ))\), then we have\(\mu = \lambda - \sigma \).

     

Remark 3

(i) For \(\sigma = 2 < \lambda\) (≤28), \(\mu = \lambda - 2\) in (8), (13) and (14), since
$$ B(\lambda - 2,2) = \frac{\varGamma (\lambda - 2)\varGamma (2)}{\varGamma ( \lambda )} = \frac{\varGamma (\lambda - 2)}{(\lambda - 1)(\lambda - 2) \varGamma (\lambda - 2)} = \frac{1}{(\lambda - 1)(\lambda - 2)}, $$
we have the following equivalent reverse inequalities with the best possible constant factor \(\frac{1}{(\lambda - 1)(\lambda - 2)}\):
$$\begin{aligned}& \int _{0}^{\infty } \sum_{n = 1}^{\infty } \frac{f(x)a_{n}}{(x + n)^{ \lambda }} \,dx > \frac{1}{(\lambda - 1)(\lambda - 2)}\biggl[ \int _{0}^{\infty } x^{p(3 - \lambda ) - 1} f^{p}(x) \,dx\biggr]^{\frac{1}{p}}\Biggl(\sum_{n = 1}^{ \infty } n^{ - q - 1} a_{n}^{q}\Biggr)^{\frac{1}{q}}, \end{aligned}$$
(23)
$$\begin{aligned}& \Biggl\{ \sum_{n = 1}^{\infty } n^{2p - 1} \biggl[ \int _{0}^{\infty } \frac{f(x)}{(x + n)^{\lambda }} \,dx \biggr]^{p}\Biggr\} ^{\frac{1}{p}}> \frac{1}{(\lambda - 1)( \lambda - 2)}\biggl[ \int _{0}^{\infty } x^{p(3 - \lambda ) - 1} f^{p}(x) \,dx\biggr]^{ \frac{1}{p}}, \end{aligned}$$
(24)
$$\begin{aligned}& \Biggl\{ \int _{0}^{\infty } x^{q(\lambda - 2) - 1}\Biggl[\sum _{n = 1}^{\infty } \frac{a _{n}}{(x + n)^{\lambda }} \Biggr]^{q} \,dx\Biggr\} ^{\frac{1}{q}}> \frac{1}{(\lambda - 1)(\lambda - 2)}\Biggl(\sum _{n = 1}^{\infty } n^{ - q - 1} a_{n}^{q} \Biggr)^{ \frac{1}{q}}. \end{aligned}$$
(25)
(ii) For \(\sigma = 2 < \lambda\) (≤28), \(\mu = \lambda - 2\) in (20), (21) and (22), we have the following equivalent reverse inequalities with the best possible constant factor \(\frac{1}{(\lambda - 1)(\lambda - 2)}\):
$$\begin{aligned}& \int _{0}^{\infty } \sum_{n = 1}^{\infty } \frac{F(x)a_{n}}{(1 + xn)^{ \lambda }} \,dx > \frac{1}{(\lambda - 1)(\lambda - 2)}\biggl( \int _{0}^{\infty } x^{ - p - 1} F^{p}(x) \,dx\biggr)^{\frac{1}{p}}\Biggl(\sum_{n = 1}^{\infty } n^{ - q - 1} a_{n}^{q}\Biggr)^{\frac{1}{q}}, \end{aligned}$$
(26)
$$\begin{aligned}& \Biggl\{ \sum_{n = 1}^{\infty } n^{2p - 1} \biggl[ \int _{0}^{\infty } \frac{F(x)}{(1 + xn)^{\lambda }} \,dx \biggr]^{p}\Biggr\} ^{\frac{1}{p}}> \frac{1}{(\lambda - 1)( \lambda - 2)}\biggl( \int _{0}^{\infty } x^{ - p - 1} F^{p}(x) \,dx\biggr)^{ \frac{1}{p}}, \end{aligned}$$
(27)
$$\begin{aligned}& \Biggl\{ \int _{0}^{\infty } x^{2q - 1}\Biggl[\sum _{n = 1}^{\infty } \frac{a_{n}}{(1 + xn)^{\lambda }} \Biggr]^{q} \,dx\Biggr\} ^{\frac{1}{q}}> \frac{1}{(\lambda - 1)( \lambda - 2)}\Biggl(\sum _{n = 1}^{\infty } n^{ - q - 1} a_{n}^{q} \Biggr)^{ \frac{1}{q}}. \end{aligned}$$
(28)

5 Conclusions

In this paper, according to [20, 22], by applying the weight functions, the idea of introduced parameters and Euler–Maclaurin summation formula, a reverse half-discrete Hilbert inequality with the homogeneous kernel and the reverse equivalent forms are given in Lemma 2 and Theorem 1 (for \(p < 0\), \(0 < q < 1\)). The equivalent statements of the best possible constant factor related to some parameters are proved in Theorem 2. As applications, two corollaries about the reverse cases of the non-homogeneous kernel and some particular cases are considered in Corollary 1, Corollary 2 and Remark 3. The lemmas and theorems provide an extensive account of this type of inequalities.

Notes

Authors’ contributions

BY carried out the mathematical studies, participated in the sequence alignment and drafted the manuscript. AW and QC participated in the design of the study and performed the numerical analysis. All authors read and approved the final manuscript.

Funding

This work is supported by the National Natural Science Foundation (No. 61772140), and Science and Technology Planning Project Item of Guangzhou City (No. 201707010229). We are grateful for their help.

Competing interests

The authors declare that they have no competing interests.

References

  1. 1.
    Hardy, G.H., Littlewood, J.E., Polya, G.: Inequalities. Cambridge University Press, Cambridge (1934) zbMATHGoogle Scholar
  2. 2.
    Yang, B.C.: The Norm of Operator and Hilbert-Type Inequalities. Science Press, Beijing (2009) Google Scholar
  3. 3.
    Yang, B.C.: Hilbert-Type Integral Inequalities. Bentham Science Publishers Ltd. (2009) Google Scholar
  4. 4.
    Yang, B.C.: On the norm of an integral operator and applications. J. Math. Anal. Appl. 321, 182–192 (2006) MathSciNetzbMATHCrossRefGoogle Scholar
  5. 5.
    Xu, J.S.: Hardy–Hilbert’s inequalities with two parameters. Adv. Math. 36(2), 63–76 (2007) MathSciNetGoogle Scholar
  6. 6.
    Yang, B.C.: On the norm of a Hilbert’s type linear operator and applications. J. Math. Anal. Appl. 325, 529–541 (2007) MathSciNetzbMATHCrossRefGoogle Scholar
  7. 7.
    Xie, Z.T., Zeng, Z., Sun, Y.F.: A new Hilbert-type inequality with the homogeneous kernel of degree −2. Adv. Appl. Math. Sci. 12(7), 391–401 (2013) MathSciNetzbMATHGoogle Scholar
  8. 8.
    Zhen, Z., Raja Rama Gandhi, K., Xie, Z.T.: A new Hilbert-type inequality with the homogeneous kernel of degree −2 and with the integral. Bull. Math. Sci. Appl. 3(1), 11–20 (2014) Google Scholar
  9. 9.
    Xin, D.M.: A Hilbert-type integral inequality with the homogeneous kernel of zero degree. Math. Theory Appl. 30(2), 70–74 (2010) MathSciNetGoogle Scholar
  10. 10.
    Azar, L.E.: The connection between Hilbert and Hardy inequalities. J. Inequal. Appl. 2013, 452 (2013) MathSciNetzbMATHCrossRefGoogle Scholar
  11. 11.
    Batbold, T., Sawano, Y.: Sharp bounds for m-linear Hilbert-type operators on the weighted Morrey spaces. Math. Inequal. Appl. 20, 263–283 (2017) MathSciNetzbMATHGoogle Scholar
  12. 12.
    Adiyasuren, V., Batbold, T., Krnic, M.: Multiple Hilbert-type inequalities involving some differential operators. Banach J. Math. Anal. 10, 320–337 (2016) MathSciNetzbMATHCrossRefGoogle Scholar
  13. 13.
    Adiyasuren, V., Batbold, T., Krnić, M.: Hilbert-type inequalities involving differential operators, the best constants and applications. Math. Inequal. Appl. 18, 111–124 (2015) MathSciNetzbMATHGoogle Scholar
  14. 14.
    Rassias, M.Th., Yang, B.C.: On half-discrete Hilbert’s inequality. Appl. Math. Comput. 220, 75–93 (2013) MathSciNetzbMATHGoogle Scholar
  15. 15.
    Yang, B.C., Krnic, M.: A half-discrete Hilbert-type inequality with a general homogeneous kernel of degree 0. J. Math. Inequal. 6(3), 401–417 (2012) MathSciNetzbMATHGoogle Scholar
  16. 16.
    Rassias, M.Th., Yang, B.C.: A multidimensional half-discrete Hilbert-type inequality and the Riemann zeta function. Appl. Math. Comput. 225, 263–277 (2013) MathSciNetzbMATHGoogle Scholar
  17. 17.
    Rassias, M.Th., Yang, B.C.: On a multidimensional half-discrete Hilbert-type inequality related to the hyperbolic cotangent function. Appl. Math. Comput. 242, 800–813 (2013) MathSciNetzbMATHGoogle Scholar
  18. 18.
    Huang, Z.X., Yang, B.C.: On a half-discrete Hilbert-type inequality similar to Mulholland’s inequality. J. Inequal. Appl. 2013, 290 (2013) MathSciNetzbMATHCrossRefGoogle Scholar
  19. 19.
    Yang, B.C., Lebnath, L.: Half-Discrete Hilbert-Type Inequalities. World Scientific, Singapore (2014) CrossRefGoogle Scholar
  20. 20.
    Krnic, M., Pecaric, J.: Extension of Hilbert’s inequality. J. Math. Anal. Appl. 324(1), 150–160 (2006) MathSciNetzbMATHCrossRefGoogle Scholar
  21. 21.
    Adiyasuren, V., Batbold, T., Azar, L.E.: A new discrete Hilbert-type inequality involving partial sums. J. Inequal. Appl., 2019, 127 (2019) MathSciNetCrossRefGoogle Scholar
  22. 22.
    Hong, Y., Wen, Y.: A necessary and sufficient condition of that Hilbert type series inequality with homogeneous kernel has the best constant factor. Ann. Math. 37A(3), 329–336 (2016) zbMATHGoogle Scholar
  23. 23.
    Hong, Y.: On the structure character of Hilbert’s type integral inequality with homogeneous kernel and applications. J. Jilin Univ. Sci. Ed. 55(2), 189–194 (2017) Google Scholar
  24. 24.
    Hong, Y., Huang, Q.L., Yang, B.C., Liao, J.L.: The necessary and sufficient conditions for the existence of a kind of Hilbert-type multiple integral inequality with the non-homogeneous kernel and its applications. J. Inequal. Appl., 2017, 316 (2017) MathSciNetzbMATHCrossRefGoogle Scholar
  25. 25.
    Xin, D.M., Yang, B.C., Wang, A.Z.: Equivalent property of a Hilbert-type integral inequality related to the beta function in the whole plane. J. Funct. Spaces 2018, Article ID ID2691816 (2018) MathSciNetGoogle Scholar
  26. 26.
    Hong, Y., He, B., Yang, B.C.: Necessary and sufficient conditions for the validity of Hilbert type integral inequalities with a class of quasi-homogeneous kernels and its application in operator theory. J. Math. Inequal. 12(3), 777–788 (2018) MathSciNetzbMATHCrossRefGoogle Scholar
  27. 27.
    Kuang, J.C.: Applied Inequalities. Shangdong Science and Technology Press, Jinan (2004) Google Scholar
  28. 28.
    Kuang, J.C.: Real and Functional Analysis (Continuation), vol. 2. Higher Education Press, Beijing (2015) Google Scholar

Copyright information

© The Author(s) 2019

Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.

Authors and Affiliations

  1. 1.Department of MathematicsGuangdong University of EducationGuangzhouP.R. China
  2. 2.Department of Computer ScienceGuangdong University of EducationGuangzhouP.R. China

Personalised recommendations